In Situ AFM Imaging of Adsorption Kinetics of DPPG Liposomes: A Quantitative Analysis of Surface Roughness - Duarte, Andreia A. (2020)
IF/00808/2013 (POPH, UE-FSE). M.R. acknowledges the financial support from the project PTDC/FIS-NAN/0909/2014, FCT, Portugal.